MAKTABGACHA YOSHDAGI BOLALARDA “MEN” OBRAZINING RIVOJLANISH BOSQICHLARI - Yuldasheva, G.S.; Quchqorova, N.M. (SCIENCE and SOCIETY, 2025)
The article discusses the manifestation of self-awareness in physical, social, mental, and emotional aspects, as well as the importance of developing the "I" image in students.
Keywords: personality; "I" image; self-awareness; theory; individualization; bility